Panoscopie : la photographie panoramique de Luc Courchesne - Massumi, Brian (CV Photo, 2003)
Abstract The panoramic photography of Luc Courchesne introduces, within the conventions of traditional panoramic painting, formal and technical variations that significantly alter the aesthetic basis of the genre and require a new theoretics. Formally, in Courchesne's photographs a tension is created between the slightly distorted periphery of the image and the pictorial void created at its centre by the physical presence of the camera and its panoramic lens. This imbalance induces a barely perceptible experience of movement in place, a formal vertigo, that inwardly animates the image. This intensive, or virtual, movement within the fixed image, qualifies the photographs as interactive even in the absence of actual interaction, and can be thought of, in aesthetic continuity with Courchesne's truly interactive installations, as an emergent state of interactive experience.